Factors Influencing Yield Spreads Of The Malaysian Bonds - Ahmad, Norliza; Muhammad, Joriah; Masron, Tajul Ariffin (Asian Academy of Management (AAM), 2009)
Malaysian bond market is developing rapidly but not much is understood in terms of macroeconomic factors that could influence the yield spread of the Ringgit Malaysian denominated bonds. Based on a multifactor model, this paper examines the impact of four macroeconomic factors namely: Kuala Lumpur Composite Index (KLCI), Industry Production Index (IPI), Consumer Price Index (CPI) and interest rates (IR) on bond yield spread of the Malaysian Government Securities (MGS) and Corporate Bonds (CBs) for a period from January 2001 to December 2008. The findings support the expected hypotheses that CPI and IR are the major drivers that influence the changes in MGS yield spreads. However IPI and KLCI have weak and no influence on MGS yield spreads respectively Whilst IR, CPI and IPI have significant influence on the yield spreads of CB1, CB2 and CB3, KLCI has significant influence only on the CB1 yield spread but not on CB2 and CB3 yield spreads